Strengthening Disaster Risk Communication: Insights from Emergency Operation Centers in Saudi Arabia - Jameel Abualenain (The Journal of Medicine, Law & Public Health)
Effective risk communication is essential for coordinated disaster response, particularly among Emergency Operation Center (EOC) leaders managing crises. This study assesses the perceptions of EOC leaders in Saudi Arabia regarding key risk communication challenges, focusing on clarity, transparency, and consistency. Using a purposive sample of 95 EOC leaders, the study employed a structured survey to gather data on various aspects of disaster communication. Results indicated high ratings for the clarity and accessibility of information, though transparency and consistency scored lower, revealing gaps in cross-agency communication. Notable correlations between trust, reliability, and transparency suggest that strengthening one element may reinforce others, promoting cohesive disaster response.